Mossàrabs de València i «llengua mossàrab» - Barceló, Carme (Caplletra. Revista Internacional de Filologia, 1996)
Since the publication of Simonet's Glosario (1888) some scholars have been collecting data of sustain the hipothetical presence of Mozarab communities and the use of a Romance Language in the Valencian area under Islam. We show in this paper how they have commited abuses and arbitrarieties on the material and we interpret it in his true historical context.